Elevated pro-BNP and low-grade inflammation are associated with low bone mineral density in systemic sclerosis, a case control study - Kerstin Lillpers; Kristofer Andréasson; Seyed Morteza Najibi; Anthony D Woolf; Roger Hesselstrand; Kristina E Åkesson; Meliha C Kapetanovic (Arthritis Research & Therapy, 2026)
Abstract Background Bone mineral density (BMD) is compromised in patients with systemic sclerosis (SSc) compared to the background population, yet the underlying disease related factors are less known. This study evaluates SSc disease-related features and predictability for BMD along with established risk factors for low BMD in SSc patients compared to controls. Methods The study includes 211 SSc patients, 182 women and 29 men (mean age 61 yrs, mean disease duration 9 yrs) regularly followed at the Skåne University Hospital, Lund, Sweden and 505 age- and sex-matched controls. Data collection: BMD hip and spine, BMI, SSc-features, biomarkers and potential risk factor questionnaire. Multinomial logistic regression analysis was used to calculate BMD odds ratio (OR); multiple linear regression for associations between T-score and SSc-related variables and lifestyle factors; and machine learning to fit a model to predict total hip T-score in SSc. Results NT-proBNP and elevated CRP were independently associated with low BMD in SSc patients (p